Capsid protein structure in Zika virus reveals the flavivirus assembly process - Ter Yong Tan (Nature Portfolio, 2020)
The structure of flavivirus surface proteins has been elucidated, but the conformation of capsid proteins within particles is less clear. Here, the authors provide a subnanometer resolution structure of Zika virus capsid protein within the virus particle, elucidating its quaternary organization and role in flavivirus packaging.